Motivation among Teenage Football Players: A Longitudinal Investigation throughout a Competitive Season - Rodrigues, Filipe (2023)
The present study aimed to investigate the dynamic changes in behavioral regulations among teenage football players throughout a competitive season, with three measurement points (T1, T2, and T3). The total sample size for the study comprised 108 participants (78 male; 30 female). The participants’ mean age was 14.31 (SD = 1.48). A MANOVA repeated measures analysis was performed within the group for all six behavioral regulations based on self-determination theory. The results of the study revealed noteworthy patterns in the behavioral regulations and intrinsic motivation scores over the competitive season. Identified regulation demonstrated a significant increase from T1 to T3 (p < 0.01, η2p = 0.13). Intrinsic motivation displayed a significant decrease over the same period from T1 to T3 (p < 0.01, η2p = 0.12). On the other hand, amotivation, external regulation, introjected regulation, and integrated regulation did not show significant changes between the three time points. The findings have practical implications for coaches and sports practitioners, as they highlight the need to create a supportive and autonomy-promoting environment to sustain athletes’ intrinsic motivation throughout a competitive season. Also, recognizing the increase in identified regulation can inform strategies that align team goals and training sessions with players’ individual values, thereby enhancing their commitment and dedication to the team’s success